Knowledge and Attitude of Homeopathy Doctors Attending the Modern Pharmacology Bridge Course toward Psychiatry - A Cross-sectional Study - Deepti Saka; Ramdas Ransing; Sagar Subhash Nanaware; Krishna Pevekar; Kumari Padma (Wolters Kluwer Medknow Publications, 2024)
Aim: The aim of the study is to assess the knowledge and attitude of homeopathy doctors attending modern pharmacology course toward psychiatry. This is the first ever course approved by the state government of Maharashtra in India for registered homeopathy practitioners. We have considered them as our study group because they work at a grassroots level and are the first level of contact between the individual and the health system. Methodology: One hundred subjects were included in the study. A semi-structured questionnaire was used to assess their knowledge and attitude toward psychiatry. Informed consent was obtained from all the participants. Results: Of the 48 participants included in the study, most belonged to ages 44-53 years, with 83.4% of males. All had completed a degree before 2000 AD with about 50% of the sample having completed a bachelor's degree. Of these, 74.5% had more than 20 years of homeopathic practice. Based on the Attitudes Toward Psychiatry-30 questionnaire, majority of the sample had a negative attitude toward psychiatry. Conclusion: Most of the traditional homeopathy doctors carry a negative or neutral attitude toward the field of psychiatry and its therapeutic interventions.